ADDING DIFFERENT LEVELS OF TURMERIC POWDER AND CURCUMIN IN THE DIET ON SOME SERUM BIOCHEMICAL OF BROILER REARED UNDER NORMAL AND HEAT STRESS CONDITIONS - Mustafa, M. M.; Karadas, F.; Tayeb, I. T. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was carried out to elucidate the effect of supplementing different levels of turmeric powder and curcumin on serum lipid profile, protein, thyroid hormones (T3 and T4), ALT, AST enzymes, uric acid, creatine kinase and glucose. Seven-hundred and fifty chicks Ross 308, received from a local hatchery. Chicks divided into two groups, normal and heat stressed conditions, with 5 treatments and 3 replicates in which 25 chicks for each. The dietary treatments composed of basal diet (control), 50 g curcumin/ton, 75 g curcumin/ton, 1.65 kg turmeric powder/ton and 2.5 kg turmeric powder/ton. Results showed that adding turmeric powder and curcumin had significant effects (P<0.05) on serum lipid profile, protein profile, T3, T4, ALT enzyme, creatine kinase, uric acid and glucose. Concerning the rearing condition, which had a significant effect (P<0.05) on the serum cholesterol, LDL, total protein, albumin, T3 hormone, ALT, AST enzymes, creatine kinase, uric acid and glucose.